Peygamberlerin mesajındaki bütünlük açısından Saff Suresi Tefsiri ve Hz. Muhammed (SAV)’in durumu - Kiraz, Celil (My University, 2000)
Tezimiz bir giriş ve iki bölümden oluşmaktadır. Tez, Yrd. Doç. Dr. Emin Işık danışmanlığında yapılmıştır. 159 sayfadan ibarettir. Tezimizin Giriş bölümünde, tefsir, sûre ve sûre tefsiri kavramları hakkında bilgi verilmiş; sûre tefsiri alanında daha önce yapılmış çalışmalar, mümkün olduğunca bir araya getirilmeye çalışılmıştır. ncelikle, peygamberlerin mesajının kaynak ve muhtevâ olarak birliği ve bütünlüğü üzerinde durulmuştur. Burada, bütün peygamberlerin Allah'tan vahiy aldıkları, O'nun tarafından peygamberlikle görevlendirildikleri konusu işlenmiştir. Bütün vahiylerin kaynağı, asıl sahibi Allah olduğuna göre, bu vahiylerin birbirine benzemesi kadar doğal bir şey yoktur. Şu an elimizde bulunduğu şekliyle bile bu kutsal kitaplar, birçok konuda benzerlikler içermektedirler. Bu bölümün başında, bu kutsal kitapların benzerliklerine örnekler verdik. Aynı bölümde, Saff Sûresi hakkında genel bilgilere de yer verdik; sûrenin isimleri, âyet, kelime ve harf sayısı, sûrenin nüzûl sebepleri, önceki ve sonraki sûreyle ilgisi, sûrenin konuları gibi başlıklar altında bu genel bilgileri topladık. Daha sonra sûrenin tefsirine geçtik. İkinci Bölüm'de, Hz. Peygamber'in, peygamberlerin mesajının bütünlüğü içerisindeki konumu işlenmektedir. Bu başlık altında, onun önceki kutsal kitaplarda müjdelenmesi, son peygamber oluşu ve risaletinin evrenselliği üzerinde durulmuştur. Hz. Peygamber'in önceki kutsal kitaplarda müjdelendiği, geleceğinin önceden haber verildiği görüşü, Kur'an kaynaklı bir görüştür. Bu bölümün hemen başında, tebşîrât konusunun İslâmî kaynaklardaki temelleri anlatılmıştır. Daha sonra, kadîm kitaplardaki, Ahd-i Atik'teki, Ahd-i Cedit'teki ve Barnabas İncili'ndeki müjdeler sayılmıştır. Kadîm kitaplardan kastımız, Hinduizm'in, Zerdüşlük'ün ve Budizm'in kutsal kitaplarıdır. Bu kitaplardaki müjdelere geçilmeden önce, bu kitapların ilâhî kaynaklı olduğunu gösteren delillere yer verilmiştir. Yine İkinci Bölüm'de, Hz. Peygamber'in son peygamber oluşunun delilleri sayıldıktan sonra, bunun hikmetleri üzerinde de durulmuştur. Daha sonra, onun risaletinin evrenselliği konusu, delilleriyle işlenmiş ve bunun hikmetleri de anlatılmıştır.

OF THE HIGH LISANS THESIS The thesis is made up of an introduction and two parts. The thesis was made under the advicement of Assistant to Assosiate Professor (Yrd. Doç. Dr.) Emin Işık. It is made up of 159 pages. It is given some information about the interpretation, sura and the sura interpretation at the İntroduction part of my thesis. Insofar as it's possible, the studies of the sura interpretations that made once have tried to be collected. At the First Part, before all else, it is stand at the unity and wholeness of the message of the prophets sourcely and contently. It is worked up at this part that the all prophets has been sent by The God and they have given revelation from him. If the source of whole revelations and their real owner is God, there is no unusualness at the similarity of these revelations. These sacred books, even their condition that they are now in, have content similarities at a lot of subject. At the beginning of this part, I have given some examples about the similarities of these sacred books. At the same part, I included general informations about the Saff Sura; I collected these general informations under that titles: Sura's names, its verse, vocabulary and letter numbers, reasons of the revelation of the Sura, its connections with the last and the next suras and the subjects of the sura. And then, I passed to the interpretation of the sura. At the Second Part, it is worked up the condition of the Prophet Mohammed in the wholeness of the message of the prophets. Under this title, it is talked about the coming of him at the former sacred books, his becoming the last prophet and his prophethood's becoming universal. The opinion of that the Prophet Mohammed has been talked about him and given news about him at the former sacred books, is originated from The Koran. At the top of this part, it is talked about the foundations of being gived good news about the Prophet Mohammed. And then, it is set out the good news that exists in the ancient books, The Old Testament, The New Testament and The Evangel of Barnabas about the Prophet Mohammed. My intention with the 'ancient books' is the sacred books of Hinduism, Zoroastrianism and Buddhism. Before that the good news which exists in these books is set out, I included the proofs about that these books are divine originated. At the Second Part again, after being listed the proofs of the prophecies of the Prophet Mohammed, it is made mention of wisdom of this. And then, it is worked up his prophecy's universality subject with its proofs and the wisdom of that even. Advicer: Yrd. Doç. Dr. Emin Işık
Keywords: İslamiyet-Saff Suresi; Muhammed, Hz; Peygamberler